Glycogen metabolism regulates macrophage-mediated acute inflammatory responses - Jingwei Ma (Nature Portfolio, 2020)
Glycogen can be metabolized via glycogenolysis and the pentose phosphate pathway as well as into the production of UDP glucose, which when secreted can bind the P2Y14 receptor. Here the authors show how these glycogen metabolism pathways contribute to proinflammatory macrophage activation and susceptibility to sepsis.